Validation of smartphone free heart rate monitoring application during treadmill exercise (Validação de aplicativo gratuito de smartphone para monitoramento da frequência cardíaca durante exercício em esteira) (Validación de aplicación gratuita de smartphone para monitorización de la frecuencia cardíaca durante ejercicio en cinta) - Jaafar, Zulkarnain; Murugan, Aravind Kumar (Sociedade Brasileira de Medicina do Exercício e do Esporte, 2019)
Objective: The number of people participating in leisure sports activities and amateur competitions has been rising sharply. Free smartphone heart rate monitoring applications are readily available for use; however, information on their accuracy during exercise is still limited. Therefore, the purpose of our study was to validate a smartphone free heart rate monitoring application during treadmill exercise in healthy individuals. Methods: This was a prospective experimental study testing the free heart rate app ‘INSTANT HEART RATE: AZUMIO.’ Twenty-seven healthy participants were requested to perform the treadmill task with four different workloads: walking at 2.0 mph, walking at 3.5 mph, jogging at 4.5 mph and running at 6.0 mph. Participants had to perform the exercises for 3 minutes for each workload, and heart rates were recorded using the smartphone app and ECG at rest, during the exercise and recovery periods at each 60-second interval. Results: Heart rates measured using the free smartphone app at rest, walking at 2.0 mph, brisk walking at 3.5 mph, slow jogging at 4.5 mph and recovery stage were accurate with correlation coefficient value ≥0.95 and standard error of estimate <1 bpm. However, the correlation values during running at 6 mph were inconsistent with a standard error of estimate >5 bpm. Conclusion: The free smartphone app that we tested accurately estimates heart rate at rest, during low to moderate intensity exercise and the recovery period, but becomes less consistent during high-intensity exercise, making this app suitable for use during indoor activities of low to moderate intensity. Level of evidence II; Diagnostic Studies - Investigating a diagnostic test. © 2019, Redprint Editora Ltda. All rights reserved.